ANALYSIS OF THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY (CSR) PROGRAMS ON CORPORATE IMAGE IN THE DIGITAL ERA - Hodijah, Cucu; Kusnara, Hasti Pramesti; Albar, Fauzan Manafi; Gusyana, Dadang; Jaya, Umban Adi (JURNAL ILMIAH EDUNOMIKA, 2024)
In the digital era, corporate image is impacted not only by the social and environmental effects of CSR programs but also by the public communication of these programs. As a result, corporate social responsibility, or CSR, has become a crucial component of company strategy around the globe. Information and communication technology advancements give businesses excellent chances to connect with a larger audience via a variety of digital channels. This emphasizes how crucial it is to assess how well CSR initiatives contribute to a company's favorable public image in the digital age. This study aims to determine the impact of CSR programs on corporate image, focusing on PT Amerta Indah Otsuka's CSR initiatives in Sukabumi. This study aims to analyze how PT Amerta Indah Otsuka's CSR programs affect corporate image, especially in terms of communication and public response in the digital era. The findings are expected to provide guidance for other companies in designing effective CSR strategies in an increasingly connected digital world. The literature review highlights that effective CSR management not only enhances corporate image but also contributes to competitive and financial advantages. Studies emphasize that CSR increases customer loyalty, strengthens brand identity, and improves financial performance. In addition, CSR initiatives also improve employee satisfaction and regulatory relations, support risk management, and sustainability efforts. The methodology used was an associative causal quantitative approach, by collecting data through a Google Form-based questionnaire distributed to 100 respondents aged 18-65 years in Sukabumi. Statistical analysis, specifically regression analysis using SPSS, confirmed a significant positive relationship between CSR and the dependent variable, indicating a substantial influence of CSR on corporate image.